A micro-arc oxidation composite coating for marine environment and preparation method thereof

By performing microarc oxidation treatment on the surface of the light alloy and using silane modified resin and hexagonal boron nitride nanomaterial for pore sealing treatment, the problem of poor friction corrosion resistance of light alloys in the marine environment is solved, and the wear resistance and corrosion resistance of the coating are significantly improved, providing technical support for marine engineering equipment.

CN118326475BActive Publication Date: 2025-04-04GUANGZHOU MARITIME INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410435926.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2025-04-04
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

Light alloys show poor friction corrosion resistance due to friction and corrosion in marine environments. The existing anticorrosion coatings are prone to damage. The high-cost PVD technology is not suitable for complex workpieces. Ion permeation and heat treatment also have performance impacts.

Method used

After microarc oxidation treatment on the surface of the light alloy, a silane-modified resin is used as the pore sealing agent, and a two-dimensional nanomaterial hexagonal boron nitride is added to improve the roughness, porosity and friction coefficient of the coating and improve its friction corrosion resistance in marine environments.

Benefits of technology

It significantly reduces the friction coefficient and corrosion current of the micro-arc oxidation coating, improves the impermeability and wear resistance of the coating, comprehensively improves the friction corrosion resistance of the micro-arc oxidation coating, and provides technical support for the application of light alloys in marine engineering equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118326475B_ABST
    Figure CN118326475B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a micro-arc oxidation composite coating for use in a marine environment, comprising the following steps: step one, substrate treatment; step two, surface micro-arc oxidation treatment of the substrate; step three, sealing treatment of the substrate after micro-arc oxidation treatment; step four, static curing of the sealed substrate to obtain a micro-arc oxidation composite coating. The composite coating prepared by the method of the present invention has excellent friction and corrosion resistance, and its corrosion current, friction coefficient and wear rate in a simulated seawater solution are greatly reduced compared with aluminum alloy substrates, ordinary micro-arc oxidation coatings and micro-arc oxidation coatings that are only sealed with silane, which comprehensively improves the friction and corrosion resistance of the micro-arc oxidation coating, and provides technical support for the further application of light alloys in marine engineering equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a composite coating and a preparation method thereof, in particular, a micro-arc oxidation composite coating for marine environment and a preparation method thereof, belonging to the technical field of metal material surface treatment. Background Art

[0002] The ocean covers 70% of the earth's surface and has abundant resources. In order to develop and utilize these resources, people must build and use various marine equipment, such as oil drilling platforms, submarines, ships, etc. Most of these equipment are made of metal structural materials. However, the high salinity, humidity, temperature changes and microbial activity of the marine environment will cause various metal materials to face corrosion problems during use. In addition, marine engineering equipment will inevitably suffer from friction and wear under mechanical stress during operation. Wear and corrosion in seawater environments usually produce alternating coupling effects on metal materials, leading to the occurrence of tribocorrosion. During the friction process, the surface of the material will continuously expose new material surfaces due to wear, and these new surfaces are more susceptible to corrosive media in the marine environment, such as oxygen and chloride ions. At the same time, the thermal effects and mechanical stresses in the wear process may also accelerate the chemical or electrochemical reactions, thereby accelerating the corrosion process. In turn, the corrosion process will also reduce the mechanical properties of the material, making it more susceptible to friction and wear; in addition, corrosion products may accumulate on the surface of the material to form a wear medium, further aggravating the wear process. The friction corrosion process will further accelerate the erosion process of equipment materials on the basis of friction and corrosion, thereby reducing the service life of marine engineering equipment, increasing maintenance and replacement costs, and may even cause serious consequences such as equipment damage and safety accidents.

[0003] Light alloys, such as aluminum alloys, magnesium alloys, titanium alloys, etc., are widely used in aerospace, automobile manufacturing, electronic equipment and other industries due to their light weight, high specific strength, good mechanical processing performance and other advantages. Although light alloys have many excellent properties, the mechanical strength and wear resistance of the light alloy surface are generally poorer than those of traditional materials such as steel, especially when serving in highly corrosive marine environments, the friction and corrosion resistance of light alloys is poor. Although researchers have tried many methods to improve their corrosion resistance and friction resistance, including using different alloy elements, using anti-corrosion coatings, or improving their performance through heat treatment and other surface treatment technologies. However, these methods all have some shortcomings, such as: the anti-corrosion coating coating is easily damaged by external wear, which leads to a decrease in corrosion resistance and coating failure; the coating prepared by PVD technology has good wear resistance and corrosion resistance, but the technical cost is high and it is not convenient to handle complex workpieces; ion penetration and heat treatment rely on high temperature conditions, which are easy to affect the overall performance of the substrate, etc.

[0004] Micro-arc oxidation (MAO) is a technology that uses micro-arc discharge in an electrolyte to generate a ceramic coating on a metal surface in situ. The micro-arc oxidation coating has the characteristics of high hardness, certain corrosion resistance and good bonding strength, and is a surface protective coating with good performance. However, the micro-arc oxidation coating also has some disadvantages, such as high surface roughness, large porosity, and many cracks. These defects will make the friction coefficient of the coating surface high and the corrosion resistance insufficient. Under working conditions where friction and corrosion are simultaneously encountered, the surface of the micro-arc oxidation coating is easily consumed and damaged by wear; at the same time, due to the porous characteristics of the surface of the micro-arc oxidation coating, the corrosive liquid can easily penetrate into the coating structure, further accelerating the failure of the coating. Therefore, it is necessary to improve or compositely treat the micro-arc oxidation coating to reduce its surface roughness, porosity and friction coefficient, thereby improving its friction and corrosion resistance in the marine environment. Summary of the invention

[0005] In view of the shortcomings of the above technologies, the present invention intends to use silane-modified resin as a sealing agent for the micro-arc oxidation coating on the basis of micro-arc oxidation treatment of the light alloy surface, and add two-dimensional nanomaterial hexagonal boron nitride therein, so as to simultaneously improve the roughness and porosity of the micro-arc oxidation coating surface, so that the friction coefficient of the micro-arc oxidation coating in seawater is greatly reduced, and the impermeability of the coating is significantly improved, thereby comprehensively improving the friction and corrosion resistance of the micro-arc oxidation coating, and providing technical support for the further application of light alloys in marine engineering equipment.

[0006] To this end, the first technical solution provided by the present invention is as follows:

[0007] A method for preparing a micro-arc oxidation composite coating for use in a marine environment comprises the following steps:

[0008] Step 1: substrate processing;

[0009] Step 2, performing micro-arc oxidation treatment on the surface of the substrate;

[0010] Step 3, sealing the substrate after micro-arc oxidation treatment;

[0011] Step 4: Allow the sealed substrate to stand and solidify to obtain a micro-arc oxidation composite coating.

[0012] Furthermore, the substrate treatment process in step 1 is sequentially degreasing and cleaning, grinding and polishing, ultrasonic cleaning, and drying.

[0013] Furthermore, the degreasing cleaning is performed on the substrate using a degreasing agent.

[0014] Furthermore, the degreasing agent comprises the following components in parts by weight: 2-4 parts by weight of sodium fatty acid methyl ester ethoxylate sulfonate, 11-12 parts by weight of benzotriazole, 6-9 parts by weight of tetramethylammonium hydroxide, 1-5 parts by weight of linear imidazoline amide, 15-20 parts by weight of sodium lignin sulfonate, 20-30 parts by weight of oleyl alcohol polyglycol ether and 15-20 parts by weight of a mixture of carbonyl alcohol ethoxylates, and 70-100 parts by weight of deionized water.

[0015] Furthermore, the grinding and polishing process is to use 200#, 400#, 800#, 1200#, and 2000# SiC sandpaper to grind and polish the surface of the substrate step by step.

[0016] Furthermore, the ultrasonic cleaning time is 1-10 minutes.

[0017] Furthermore, in the step 2, the process of performing micro-arc oxidation treatment on the surface of the substrate is to prepare an electrolyte and perform micro-arc oxidation treatment on the surface of the substrate using a pulse power supply.

[0018] Furthermore, the electrolyte is prepared by using an aqueous solution of one or more of phosphates, silicates, and aluminates.

[0019] Furthermore, the micro-arc oxidation process parameters in step 2 are: a current density of 5A / dm 2 -20A / dm 2 , stirring speed is 200-500rpm, frequency is 100Hz-2000Hz, duty cycle is 10%-80%, temperature is below 55°C, and time is 2min-30min.

[0020] Furthermore, the micro-arc oxidation coating has a thickness of 5 μm to 50 μm.

[0021] Furthermore, in the step three, the process of sealing the substrate after the micro-arc oxidation treatment is to prepare a silane-modified resin dispersion and apply the silane-modified resin dispersion to the surface of the substrate after the micro-arc oxidation treatment.

[0022] Furthermore, the ingredients of the silane-modified resin dispersion in step three are 20-50 parts of tetraethyl orthosilicate, 20-50 parts of silane coupling agent, 0.5-5 parts of maleic anhydride, 10-30 parts of polyurethane resin, 40-100 parts of solvent, and 0.1%-10% of hexagonal boron nitride two-dimensional nanosheets 0.1-10 parts.

[0023] Furthermore, the ratio of tetraethyl orthosilicate to the silane coupling agent is 1:10 to 10:1.

[0024] Furthermore, the ratio of maleic anhydride to polyurethane resin is 1:10 to 10:1.

[0025] Furthermore, the solvent is xylene and ethanol.

[0026] Furthermore, the size of the hexagonal boron nitride two-dimensional nanosheet is 50nm to 1μm.

[0027] Furthermore, the conditions for static curing in step 4 are temperature 10-40°C, time 36-48h or temperature 60-150°C, time 12-24h.

[0028] The second technical solution provided by the present invention is: a micro-arc oxidation composite coating for marine environment, wherein the composite coating is prepared by any of the above-mentioned preparation methods of the micro-arc oxidation composite coating for marine environment.

[0029] Furthermore, the composite coating has a thickness of 5 μm-60 μm.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The outer layer of the composite coating prepared by the method of the present invention is a silane-modified resin coating containing boron nitride nanoparticles, which can fill the gaps generated by the porous structure in the inner micro-arc oxidation layer and has excellent bonding strength with the micro-arc oxidation ceramic layer due to the anchoring effect.

[0032] 2. In a corrosive environment, the sealing effect of the silane-modified resin can significantly improve the corrosion resistance of the micro-arc oxidation coating; the boron nitride nanosheets in the coating have excellent physical barrier properties unique to two-dimensional materials, and due to their own hydrophobic properties, they can further resist the intrusion of corrosive media such as seawater.

[0033] 3. Under wear conditions, the micro-arc oxidation coating mainly composed of ceramic components has the characteristics of high hardness and can play a mechanical support role; silane-modified resin and nano-boron nitride fill the gaps in the micro-arc oxidation coating, and can continuously form a lubricating surface transfer film during the friction process, effectively reducing the friction coefficient and the wear rate of the coating.

[0034] 4. Under friction corrosion conditions, the composite coating prepared by the method of the present invention has excellent friction corrosion resistance. Its corrosion current, friction coefficient and wear rate in simulated seawater solution are greatly reduced compared with those of aluminum alloy substrate, ordinary micro-arc oxidation coating and micro-arc oxidation coating with only silane sealing. The friction corrosion resistance of the micro-arc oxidation coating is comprehensively improved, providing technical support for the further application of light alloys in marine engineering equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of the structure of the micro-arc oxidation composite coating;

[0036] Figure 2 The surface morphologies of the uncoated and sealed micro-arc oxidation coating (a) in Comparative Example 1 and the composite coating (b) in the embodiment under a scanning electron microscope;

[0037] Figure 3 Potentiodynamic polarization curves of 2024 aluminum alloy substrate, comparative example 1, comparative example 2 and embodiment obtained by immersing in 3.5wt.% NaCl solution for 10 minutes;

[0038] Figure 4 The wear scar morphology of the surface of 2024 aluminum alloy substrate, comparative example 1, comparative example 2 and embodiment after 2 hours of friction and wear test in 3.5wt.% NaCl solution;

[0039] Figure 5 It is a graph showing the calculation results of the surface wear rate of the 2024 aluminum alloy substrate, comparative example 1, comparative example 2 and the embodiment after a friction and wear test in a 3.5wt.% NaCl solution for 2 hours;

[0040] Figure 6 It is a graph showing the change of friction coefficient over time during the friction and wear test of 2024 aluminum alloy substrate, comparative example 1, comparative example 2 and embodiment in 3.5wt.% NaCl solution for 2h;

[0041] Figure 7 This is a graph showing the change in open circuit potential over time during a friction and wear test of 2024 aluminum alloy substrate, Comparative Example 1, Comparative Example 2 and an embodiment in a 3.5 wt. % NaCl solution for 2 hours. DETAILED DESCRIPTION

[0042] The following is a further detailed description of the claims of the present invention in conjunction with specific implementation methods, but does not constitute any limitation to the present invention. Any limited modifications made by anyone within the scope of protection of the claims of the present invention are still within the scope of protection of the claims of the present invention.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0044] Example

[0045] A silane-sealed micro-arc oxidation ceramic coating was prepared on the surface of 2024 aluminum alloy by micro-arc oxidation and silane dip coating, and the process was carried out as follows:

[0046] Step 1: Pre-treat the surface of 2024 aluminum alloy. Use a degreasing agent to degrease and clean the 2024 aluminum alloy. Then use different types (200#, 400#, 800#, 1200#, 2000#) of SiC sandpaper to grind and polish the surface of 2024 aluminum alloy step by step. Use ethanol and other cleaning agents to ultrasonically clean the polished 2024 aluminum alloy for 5 minutes, and then blow dry with hot air;

[0047] Step 2: Micro-arc oxidation surface treatment: Dissolve 30g / L sodium hexametaphosphate in 1L deionized water and stir thoroughly to prepare a phosphate system electrolyte. Use a pulse power supply in constant current or constant voltage mode to perform micro-arc oxidation on the surface of 2024 aluminum alloy. The micro-arc oxidation process parameters are as follows: current density is 7.5A / dm 2 , stirring speed is 300rpm, frequency is 400Hz, duty cycle is 30%, temperature is below 50℃, time is 10min. The thickness of the prepared micro-arc oxidation coating is 10μm;

[0048] Step 3: Hexagonal boron nitride / silane dispersion dip coating and sealing: 1%wt hexagonal boron nitride nanosheets (average sheet size 100nm) are added to the silane coating and ultrasonically stirred for 30 minutes to form a dispersion. The micro-arc oxidation treated substrate is immersed in the hexagonal boron nitride / silane dispersion at a speed of 1mm / s. After standing for 3 minutes, it is pulled out at a uniform speed of 0.3mm / s and dried at 120℃ for 1h.

[0049] Step 4: Place in air at 25°C for 24 hours to solidify.

[0050] In order to demonstrate the effect of the present invention, the following comparative experimental examples are given:

[0051] Comparative Example 1

[0052] The ceramic coating was prepared on the surface of 2024 aluminum alloy by micro-arc oxidation, and the process was carried out as follows:

[0053] Step 1: pre-treat the surface of the substrate, use a degreasing agent to degrease and clean the substrate, then use different types (200#, 400#, 800#, 1200#, 2000#) of SiC sandpaper to grind and polish the surface of the substrate step by step, use ethanol or other cleaning agents to ultrasonically clean the polished substrate, and then blow dry with hot air to obtain the substrate;

[0054] Step 2: Micro-arc oxidation surface treatment: Dissolve 30g / L sodium hexametaphosphate in 1L deionized water and stir thoroughly to prepare a phosphate system electrolyte. Use a pulse power supply in constant current or constant voltage mode to perform micro-arc oxidation on the substrate surface. The micro-arc oxidation process parameters are as follows: current density 7.5A / dm 2 , stirring speed is 300rpm, frequency is 400Hz, duty cycle is 30%, temperature is below 50℃, time is 10min. The thickness of the prepared micro-arc oxidation coating is about 10μm.

[0055] Comparative Example 2

[0056] A silane-sealed micro-arc oxidation ceramic coating was prepared on the surface of 2024 aluminum alloy by micro-arc oxidation and silane dip coating, and the process was carried out as follows:

[0057] Step 1: pre-treat the surface of the substrate, use a degreasing agent to degrease and clean the substrate, then use different types (200#, 400#, 800#, 1200#, 2000#) of SiC sandpaper to grind and polish the surface of the substrate step by step, use ethanol or other cleaning agents to ultrasonically clean the polished substrate, and then blow dry with hot air to obtain the substrate;

[0058] Step 2: Micro-arc oxidation surface treatment: Dissolve 30g / L sodium hexametaphosphate in 1L deionized water and stir thoroughly to prepare a phosphate system electrolyte. Use a pulse power supply in constant current or constant voltage mode to perform micro-arc oxidation on the substrate surface. The micro-arc oxidation process parameters are as follows: current density 7.5A / dm 2 , stirring speed is 300rpm, frequency is 400Hz, duty cycle is 30%, temperature is below 50℃, time is 10min. The thickness of the prepared micro-arc oxidation coating is about 10μm.

[0059] Step 3: Silane dip coating and sealing. Immerse the substrate after micro-arc oxidation treatment in the silane coating at a speed of 1 mm / s. After standing for 3 minutes, pull it out at a uniform speed of 0.3 mm / s. After drying at 120°C for 1 hour, place it in the air at 25°C for 24 hours to cure.

[0060] In order to better illustrate the advantages of the present invention, the verification scheme provided by the present invention is given below:

[0061] See also Figure 3-7 In order to verify the anti-corrosion performance and friction corrosion resistance of the coating prepared by the present invention, electrochemical corrosion and friction corrosion tests were carried out on the 2024 aluminum alloy substrate and the coatings prepared in Example, Comparative Example 1 and Comparative Example 2.

[0062] The electrochemical corrosion test was performed by immersing the 2024 aluminum alloy substrate, the embodiment, the comparative example 1 and the comparative example 2 in a 3.5wt.% NaCl solution for 10 min and measuring the open circuit potential (OCP). The potentiodynamic polarization test range was -0.5V-1V vs. OCP, and the scanning speed was 1mV / s. The potentiodynamic polarization curve obtained in the experiment is shown in the attached Figure 3 The corrosion current of the example sample is reduced by about 5 orders of magnitude, 3 orders of magnitude and 1 order of magnitude compared with the 2024 aluminum alloy substrate, comparative example 1 and comparative example 2, respectively, indicating that the micro-arc oxidation composite coating containing hexagonal boron nitride nanosheets has excellent anti-corrosion performance, among which the addition of silane sealing and hexagonal boron nitride nanosheets further plays a role in significantly improving the corrosion resistance of the coating on the basis of the micro-arc oxidation layer.

[0063] The friction corrosion test was conducted by soaking the 2024 aluminum alloy substrate, the embodiment, comparative example 1 and comparative example 2 in a 3.5wt.% NaCl solution for 10 minutes, respectively. A 6mm diameter silicon nitride ceramic ball was used as a counter-wear part. A reciprocating wear test was conducted using a friction and wear testing machine. The test parameters included: applied load of 5N, reciprocating stroke of 3mm, reciprocating frequency of 5Hz, and wear time of 2h. After the wear process was completed, the test was allowed to stand for 10 minutes. During the test, data on the change of friction coefficient and open circuit potential over time were collected. After the test was completed, the surface wear scar morphology was measured and the surface wear rate data was calculated. The experimental data results are attached. Figure 4-7 . The test results show that the friction coefficient, wear scar depth and wear rate of the embodiment coating in simulated seawater are greatly reduced compared with the 2024 aluminum alloy substrate, comparative example 1 and comparative example 2, which indicates that the composite coating prepared by the preparation method provided by the present invention has better performance and can withstand friction corrosion for a long time. Among them, the friction coefficient and wear rate indicators of the embodiment are significantly reduced compared with comparative example 2, which highlights the self-lubricating effect of the addition of hexagonal boron nitride nanosheets, thereby achieving a further improvement in the friction corrosion resistance of the coating.

[0064] In summary, the composite coating prepared by the preparation method provided by the present invention has excellent friction and corrosion resistance. Its corrosion current, friction coefficient and wear rate in simulated seawater solution are greatly reduced compared with those of aluminum alloy substrate, ordinary micro-arc oxidation coating and micro-arc oxidation coating with only silane sealing. The friction and corrosion resistance of the micro-arc oxidation coating is comprehensively improved, providing technical support for the further application of light alloys in marine engineering equipment.

[0065] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a micro-arc oxidation composite coating for marine environment, characterized in that: The following steps are involved: Step 1: substrate processing; Step 2, performing micro-arc oxidation treatment on the surface of the substrate; Step 3, sealing the substrate after micro-arc oxidation treatment; Step 4: Allow the sealed substrate to stand and solidify to obtain a micro-arc oxidation composite coating. The process of sealing the substrate after micro-arc oxidation treatment in step 3 is to prepare a silane-modified resin composite dispersion containing hexagonal boron nitride nanosheets, and apply the silane-modified resin composite dispersion to the surface of the substrate after micro-arc oxidation treatment. The components of the silane-modified resin dispersion in step three are: 20-50 parts of tetraethyl orthosilicate, 20-50 parts of silane coupling agent, 0.5-5 parts of maleic anhydride, 10-30 parts of polyurethane resin, 40-100 parts of solvent, and 0.1-10 parts of hexagonal boron nitride nanosheets.

2. The method according to claim 1, characterized in that The substrate treatment process in step 1 is degreasing and cleaning, grinding and polishing, ultrasonic cleaning, and drying.

3. The method for preparing a micro-arc oxidation composite coating for a marine environment according to claim 2, characterized in that: The grinding and polishing process is to use 200#, 400#, 800#, 1200# and 2000# SiC sandpaper to grind and polish the surface of the substrate step by step.

4. The method for preparing a micro-arc oxidation composite coating for a marine environment according to claim 1, characterized in that: The process of performing micro-arc oxidation treatment on the surface of the substrate in step 2 is to prepare an electrolyte and perform micro-arc oxidation treatment on the surface of the substrate using a pulse power supply.

5. The method for preparing a micro-arc oxidation composite coating for a marine environment according to claim 4, characterized in that: The micro-arc oxidation process parameters in step 2 are: current density 5A / dm 2 -20A / dm 2 , stirring speed is 200-500rpm, frequency is 100Hz-2000Hz, duty cycle is 10%-80%, temperature is below 55°C, and time is 2min-30min.

6. The method for preparing a micro-arc oxidation composite coating for a marine environment according to claim 1, characterized in that: The conditions for static curing in step 4 are a temperature of 10-40° C. for 36-48 h or a temperature of 60-150° C. for 12-24 h.

7. A micro-arc oxidation composite coating for marine environment, characterized in that: The composite coating is prepared by the method for preparing a micro-arc oxidation composite coating for marine environment as described in any one of claims 1-6.

8. The micro-arc oxidation composite coating for marine environment according to claim 7, characterized in that: The thickness of the composite coating is 5.05 μm-60 μm.

Citation Information

Patent Citations

  • Aluminum alloy micro-arc oxidation film hole sealing treatment method

    CN116791170A